Emirates consensus recommendations on cardiovascular risk management in type 2 diabetes - Sabbour, Hani; Almahmeed, Wael; Alawadi, Fatheya; Shehab, Abdullah; Al Zubaidi, Abdulamjeed; Bashier, Alaaeldin; Ghulam, Abdul Rauf; Rashid, Fauzia; Zaky, Hosam; Heshmat Kassemn, Hussien; Adi, Jamila Bin; Tahir, Juwairia; et al. (Frontiers in Endocrinology, 2025)
The combination of heart failure and diabetes conditions is highly prevalent in the United Arab Emirates. Development and dissemination of evidence-based regional recommendations for optimal screening, treatment, and referrals of people with diabetes and high cardiovascular risk is highly important. An expert panel of diabetologists, endocrinologists, and cardiologists from the Emirates Cardiac Society and Emirates Diabetes and Endocrine Society as well as different entities in the UAE, discussed evidence and a consensus report from the American Diabetes Association to formulate recommendations that could be applied for optimal management of heart failure in people with diabetes in the UAE. The inter-relationships between diabetes and heart failure are multifactorial and symptom regular assessments and risk factor mitigation steps are essential. Routine measurement of natriuretic peptides and high-sensitivity troponins can help identify patients requiring cardiac imaging referrals respective to the balance of clinical judgment and cost implications. While SGLT2i must be an important part of the standard of care, insulin, GLP1 receptor agonists, and/or metformin can be useful for additional glycemic control. The consensus panel aims that the presented recommendations can offer guidance for an optimal framework for people with a concomitance of diabetes and high cardiovascular risk in the United Arab Emirates.